Draft Annual Plan 1986-87 Brief Outline Government of Nagaland - Planning Commission (Planning Commission, 1985)
Nagaland State lies between 25°6' and 27° Latitudes and between 93°20' and 95°15’ Longitudes covering an area of 16,579 sq. kms, (1931 Census). The State is bounded by Assam on the Western and Northern Side / Arunachal Pradesh and Burma on the North- Eastern and Eastern side. Burma on the Eastern side, and Manipur on the Southern side Excluding a small strip towards the west bordering Assam, the whole terrain of the State is hilly varying between the heights of about 900 metres and 3048 metres above sea level.
Planning and Co-ordination Department Government of Nagaland